Synthesis, Characterization of 2-azido-4-(azido (2-azido-2-( azido carbonyl)-1,3-dioxoian-4-yl)methyl)– 5-((R-azido (hydroxyl) methyl-1,3-dioxole-2-carbonyl azide. ethanol. hydrate (L-AZD) with Some Metal Complexes - Ala H. Hassn (Journal of Global Pharma Technology, 2020)
The reaction of (L- AsCl2) : Bis [O,O – 2,3, O,O – 5,6 – (chloro(carboxylic)methylidene] – L-ascorbic acid with sodium azide in ethanol with drops of distilled water has been given a new product (L-AZD), was isolated and characterized by elemental analysis (C,H,N) , 1H-NMR, mass spectra and Fourier transform (Ft-IR). The reaction of the (L-AZD) with: [VO(II), Cr(III), Mn(II), Co(II), Ni(II), Cu(II), Zn(II), Cd(II) and Hg(II)], has been investigated and was isolated as tri nuclear cluster and characterized by: Ft-IR, U. v-Visible, electrical conductivity, magnetic susceptibilities at 25 Co, atomic absorption and molar ratio. Spectroscopic evidence showed that the binding of metal ions were through azide and carbonyl moieties resulting in a six- coordinating metal ions in [Cr (III), Mn (II), Co (II) and Ni (II)]. The Vo (II), Cu (II), Zn (II), Cd (II) and Hg (II) were coordinated through azide group only forming square pyramidal for VO (II), square planar geometry for Cu (II) and tetrahedral for Zn (II), Cd (II) and Hg (II), - for Ni (II), Cr (III) complexes were calculated, the ratio of (L-AZD) to metal ions was (3:1) confirmed by metal ratio and atomic absorption spectrophotometer, magnetic moment values at (298 K) of VO (II), Cr (III), Mn (II), Co (II), Ni (II) and Cu (II) are lower than the total spin-only indicate a dominate of anti-ferromagnetic coupling between them. Keywords: Synthesis, Tri nuclear cluster, Azide.